脱式计算.脱式计算(1)-1^10-((13/14)-(11/12))*【9-(-3)^2】+(1/2)/3(2)|(1/3)-(1/4)|+|(1/4)-(1/5)|+.+|(1/20)-(1/19)|(3)99又14分之13*(-7)(4)-2^4+3*(-1)^2000-(-2)^2(5)1-2+3-4+

来源:学生作业帮助网 编辑:作业帮 时间:2024/06/23 13:45:16
脱式计算.脱式计算(1)-1^10-((13/14)-(11/12))*【9-(-3)^2】+(1/2)/3(2)|(1/3)-(1/4)|+|(1/4)-(1/5)|+.+|(1/20)-(1/19)|(3)99又14分之13*(-7)(4)-2^4+3*(-1)^2000-(-2)^2(5)1-2+3-4+

脱式计算.脱式计算(1)-1^10-((13/14)-(11/12))*【9-(-3)^2】+(1/2)/3(2)|(1/3)-(1/4)|+|(1/4)-(1/5)|+.+|(1/20)-(1/19)|(3)99又14分之13*(-7)(4)-2^4+3*(-1)^2000-(-2)^2(5)1-2+3-4+
脱式计算.
脱式计算(1)-1^10-((13/14)-(11/12))*【9-(-3)^2】+(1/2)/3
(2)|(1/3)-(1/4)|+|(1/4)-(1/5)|+.+|(1/20)-(1/19)|
(3)99又14分之13*(-7)
(4)-2^4+3*(-1)^2000-(-2)^2
(5)1-2+3-4+5-6+...+2001-2002+2003-2004.

脱式计算.脱式计算(1)-1^10-((13/14)-(11/12))*【9-(-3)^2】+(1/2)/3(2)|(1/3)-(1/4)|+|(1/4)-(1/5)|+.+|(1/20)-(1/19)|(3)99又14分之13*(-7)(4)-2^4+3*(-1)^2000-(-2)^2(5)1-2+3-4+
(1) 原式=-1-(13/14-11/12)(9-9)+1/6
=-1-0+1/6
=-5/6
(2) 原式=1/3-1/4+1/4-1/5+...+1/19-1/20
=1/3-1/20
=20/60-3/60
=17/60
(3) 原式=(100-1+13/14)*(-7)
=100*(-7)-1/14*(-7)
=-700+1/2
=-699.5
(4) 原式=-16+3-4
=-17
(5) 原式=1+3+5+...+2003-(2+4+6+...+2004)
=(1+2003)*1002/2-(2+2004)*1002/2
=1002^2-1002*1003
=1002(1002-1003)
=-1002